2017
DOI: 10.1088/1742-6596/898/5/052019
|View full text |Cite
|
Sign up to set email alerts
|

Experience in using commercial clouds in CMS

Abstract: Abstract. Historically high energy physics computing has been performed on large purposebuilt computing systems. In the beginning there were single site computing facilities, which evolved into the Worldwide LHC Computing Grid (WLCG) used today. The vast majority of the WLCG resources are used for LHC computing and the resources are scheduled to be continuously used throughout the year. In the last several years there has been an explosion in capacity and capability of commercial and academic computing clouds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This has been chosen in view of further manipulating the payloads, as explained later. Many combinations of such parameters were tested, starting from very simple ones (only low memory / low IO production jobs), to the most demanding (accept full Monte Carlo production StepChains [18], and end-user analyses). The final configuration, established after the commissioning of the 40 Gbit/s reserved link to CNAF, has demonstrated that CINECA can be used as a standard CMS facility, on which almost all the workflows can be executed.…”
Section: Cmsmentioning
confidence: 99%
“…This has been chosen in view of further manipulating the payloads, as explained later. Many combinations of such parameters were tested, starting from very simple ones (only low memory / low IO production jobs), to the most demanding (accept full Monte Carlo production StepChains [18], and end-user analyses). The final configuration, established after the commissioning of the 40 Gbit/s reserved link to CNAF, has demonstrated that CINECA can be used as a standard CMS facility, on which almost all the workflows can be executed.…”
Section: Cmsmentioning
confidence: 99%
“…The works cited above generally show that investing in a local facility is more cost-effective than using commercial clouds; it is also possible to assess the financial efficiency of using cloud resources for specific workflows. Bauerdick et al [17] performed an experiment comparing the use of a commercial cloud with workflow-specific optimization to the use of a local facility. Specifically, they compared AWS (Amazon Web Services) spot instances for analysis of CMS experiment data [9] versus the Fermilab HEPCloud [6].…”
Section: Roi On Specific Workflowsmentioning
confidence: 99%
“…The comparison showed that it is possible to get costs of commercial cloud services close to the actual costs of local facilities. But, after using over 15 million hours (approximately a month of time on a modern super-computer) they concluded, "The steady-state cost [of AWS] came to 1.4 ± 12% cents per core-hour, which is not much larger than the estimated 0.9 ± 25% cents per core-hour for the Fermilab data center" [17]. Such small differences do not sound like much, but they can accumulate over a project lifetime to a cost difference of hundreds of thousands to millions of dollars.…”
Section: Roi On Specific Workflowsmentioning
confidence: 99%
“…An AWS academic 9 to 1 matching grant was awarded to CMS that allowed the purchase of $300.000 of credits for computing, storage, and network charges for an investment of $30.000. The size of the award was based on an estimate of the cost of one month of large-scale processing [2].…”
Section: Fermilab Hepcloud Using Amazon Web Services (Aws)mentioning
confidence: 99%
“…The results are summarized in table 1. The computing performance had reached roughly equivalent value, in terms of costs cloud costs are higher, but approaching equivalence in the future [2].…”
Section: Cost Comparison -On-premises and Off-premises Resourcesmentioning
confidence: 99%